7. PERTUMBUHAN Escherichia coli YANG DIISOLASI DARI FESES ANAK AYAM BROILER TERHADAP EKSTRAK DAUN SALAM (Syzygium polyanthum [Wight.] Walp.) The Effect of Bay Leaf (Syzygium polyanthum [Wight.] Walp.) Extract on the Growth of Escherichia coli Isolated from Broiler Chicks Feces - Suci Nurul Hidayati (Jurnal Medika Veterinaria, 2016)
This study aims to find out the effect of bay leaf extract on the growth of Escherichia coli (E. coli) isolated from broiler chicks feces. A total of 5 broiler chicks from Banda Aceh were used in this study. Bay leaf used in this research was from Banda Aceh (Aceh) and Pariaman (West Sumatra). Bacteria identification was then carried out to broiler chicks feces. Once E. coli was identified, subsequently, Kirby Bauer method was done on E. coli using bay leaf extract. Bay leaf extract was diluted with 1% CMC to the concentration of 25%, 50%, and 75%. Then the paper disc was inserted into a test tube containing bay leaf extract with various concentrations. E. coli cultures grown in nutrinet broth (NB) were then swab on the surface of Mueller Hinton agar (MHA) media. Paper discs that had been soaked in various concentrations of bay leaf extract (P1, P2, and P3) and 30 mg chloramphenicol antibiotic as a positive control (P0) were stick to the surface of MHA plates added E. coli. The MHA media were then incubated at 37° C for 24 hours. The results showed that the inhibition zone of bay leaf extracts from Banda Aceh on P0, P1, P2, and P4 were 16 mm, 0 mm, 0 mm, and 0 mm, while the inhibition zone of bay leaf extract obtained from Pariaman were 15.6 mm, 0 mm, 0 mm, and 0 mm, respectively. In conclusion, bay leaf extract do not inhibit the growth of E. coli. ____________________________________________________________________________________________________________________ Key words: bay leaf, Escherichia coli, broiler chick